2004
DOI: 10.1086/426389
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Population III Binaries

Abstract: We explore the possibility for the formation of Population III binaries. The collapse of a rotating cylinder is simulated with a three-dimensional, high-resolution nested grid, assuming the thermal history of primordial gas. The simulations are done with dimensionless units, and the results are applicable to low-mass as well as massive systems by scaling with the initial density. We find that if the initial angular momentum is as small as $\beta \approx 0.1$, where $\beta$ is the ratio of centrifugal force to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…Simulations following direct cosmological initial conditions by Abel et al (2002) find a single star with no further fragmentation; however, different simulations with somewhat more artificial initial conditions (a rotating cylinder) find efficient binary formation (Saigo et al 2004). It is conceivable that at high redshifts, a WDM universe could mimic the GRB rates of a CDM universe by compensating for a loss of small-scale power with higher efficiencies of GRB production (e.g., a higher K value at high redshifts) and visa versa.…”
Section: Uncertainties In Grb Redshift Evolutionmentioning
confidence: 99%
“…Simulations following direct cosmological initial conditions by Abel et al (2002) find a single star with no further fragmentation; however, different simulations with somewhat more artificial initial conditions (a rotating cylinder) find efficient binary formation (Saigo et al 2004). It is conceivable that at high redshifts, a WDM universe could mimic the GRB rates of a CDM universe by compensating for a loss of small-scale power with higher efficiencies of GRB production (e.g., a higher K value at high redshifts) and visa versa.…”
Section: Uncertainties In Grb Redshift Evolutionmentioning
confidence: 99%
“…Uniform reheating of the filaments and voids is a characteristic of reionization and reheating from X-rays produced by remnants of the first stars accreting from the ISM at higher redshift (Venkatesan et al 2001;Ricotti & Ostriker 2004;Ripamonti et al 2008;Shull & Venkatesan 2008). X-rays could also be produced by primordial black hole binaries (Mirabel et al 2011;Saigo et al 2004). When compared to reheating by UV radiation, X-ray reheating produces noticeably darker voids.…”
Section: Approximating Cosmic Variancementioning
confidence: 99%
“…The high-redshift population of mergers of compact objects originates in populations of stars with various A&A 574, A58 (2015) metallicities, including very low ones. Previous studies of Saigo et al (2004), Machida et al (2008), Stacy & Bromm (2013), and many others have shown that in the very early Universe, where the environment was nearly metal free, binaries might have been created. A investigation of the GW background must therefore take the effects of metallicity into account.…”
Section: Introductionmentioning
confidence: 99%